Microcontroller-Based Automatic Liquid Soap Refill System Process with Circular Economy Integration - Salsabila, Helmi; Alijoyo, Antonius; A, Muhammad Syiarul (Building of Informatics, Technology and Science (BITS), 2024)
This research aims to develop a microcontroller-based automatic liquid soap refill system integrated with the concept of a circular economy. The main problem addressed is the high use of single-use soap bottles, which negatively impacts the environment. As a solution, the designed system uses sensors to detect refill needs and perform automatic refills. A microcontroller controls this process, ensuring efficiency and user convenience. Testing was conducted to assess the system's performance under various operational and environmental conditions. The test results showed that the system functions well. Additionally, using this system reduces the use of single-use soap bottles, supports environmental sustainability, and reduces the cost of purchasing new bottles. This research concludes that microcontroller-based automation technology can be integrated with the circular economy concept to produce efficient, environmentally friendly, and economical solutions. This automatic liquid soap refill system not only enhances user convenience but also contributes positively to environmental and economic sustainability. It is hoped that the research results can serve as a reference for developing other automation technologies that support the circular economy concept.